An Age Simulation Program Promoting Positive Attitudes Toward Older People in Hong Kong: Further Evidence of Integration of Natural Social Network Effects. (May 2022) - Sun, Qian; Cheung, Justin Chun Ting; Wan, Ngai Teck Alice; Pauline, Wong Shum-Yee; Lou, Vivian W. Q.
Purpose: This study examines an age simulation program in Hong Kong concerning the possible integrative impacts of an experiential education approach and contact experience within a natural social network among younger individuals.Method: A sample of 1121 younger individuals participated in this study. Structural equation modeling was used to examine the impact of the age simulation program.Results: The results of structural equation modeling indicated the effective impact of the age-simulation program on promoting positive attitudes toward older adults among the younger participants ( β = 0.28, p < .001). The significant results of contact experience highlighted the way in which familial contact experience could bring about more positive attitudes toward the older adults ( β = 0.08, p < .01) than peer group contact can ( β = −0.08, p < .05).Discussion: The protocol of the presented program could provide an actionable framework for social workers and allied professionals to launch related service plans in the communities.